ANALYSIS OF SEISMIC SHEAR WAVE VELOCITY STRUCTURE (VS) IN THE WESTERN PART OF JAVA USING HILBERT-HUANG TRANSFORM-HVSR - Amalina Widityani, Nurin
Several significant earthquakes have occurred in the south of Java Island, where the trigger was the subduction zone of the Indo-Australian Plate and the Eurasian Plate; however, based on studies conducted by seismic researchers, it was found that there was a seismic gap that has the potential for earthquakes in the future. The Western Part of Java is an area that is vulnerable to earthquake hazards due to its proximity to the Java Trench and Sunda Strait Megathrust. In addition, this area is also passed by several active land faults, such as the Cimandiri Fault, Lembang Fault, and Baribis Fault. The possibility of damaging earthquakes needs to be a concern because several areas in the western region of Java Island are dominated by alluvium deposits, which can amplify earthquake waves. To reduce the impact of the earthquake, it is necessary to analyze the dynamic response characteristics of the soil in the western region of Java Island, such as the distribution of dominant frequency values, Vs30 and engineering bedrock depth. This study applies the Hilbert-Huang Transform analysis and the Horizontal-toVertical Spectral Ratio (HVSR) method to microtremor data. Research on the Hilbert-Huang Transform (HHT) that has been conducted has shown its advantages in eliminating non-stationary transient noises that are commonly found in measurements in urban areas. It is expected that using this analysis will improve the accuracy of the HVSR curve in describing the dominant frequency of the measurement area. The results show that, regionally, the Western Region of Java Island has a dominant frequency value in the range of 0.9–7 Hz. The 1-D profile of shear seismic wave velocity (Vs) is then obtained from the inversion of the HVSR curve to calculate Vs30 values in the range of 115–400 m/s and engineering bedrock depths in the range of 100–200 m. Low frequency, low Vs30, and large engineering-depth bedrock, which is associated with soft soils and indicates high hazard potential, are found in the northern area of the Western Part of Java, the Bandung Basin, several areas in Banten Province, and several areas around volcanoes.